Western side of Lake Pedder, Tasmania, March 1971 - Truchanas, Olegas, 1923-1972. (1971)
The serpentine name here could come from the convolutions of the river in its valley, or from the serpentine rock found in this area. Small sandy beaches are exposed in isolated bay around the lake as the water level drops in summer. The Serpentine River flows out of the lake draining the water through the swamps of the Serpentine Valley, down gorges and waterfalls to the Gordon River.
Title from caption list supplied by vendor.
Inscriptions: "New[?] Pedder waters exit Serpentine R."--In pencil lower right on verso.
Also available online
Purchased from Mrs Melva Truchanas, 2006.
Keywords: Pedder, Lake (Tas.) -- Photographs; Serpentine River (Tas.) -- Photographs; Gordon River (Tas.) -- Photographs